DATASET - STEM attitudes PST. - García-Ruiz, María Cristina; Lupión-Cobos, Teresa (Universidad de Málaga, 2024)
Analysis of STEM attitudes of Primary Education pre-service teachers through social, motivational and instructional factors affecting STEM learning. It includes the datasets and the readme file.
DATASET – STEM attitudes of pre-service teachers.
R&D project PID2022-140001OA-I00, funded by MCIN/AEI/10.13039/501100011033 and FEDER, UE; RYC2020-029033-I/AEI/10.13039/501100011033, funded by MICIU/AEI/10.13039/501100011033 and ESF Investing in your future; Project “Inquiry and argumentation about socio-scientific issues from initial training. Approach to identity and professional competences” reference B4-2023-22, funded by Universidad de Málaga
Keywords: Investigación activa en educación; STEM education; STEM attitudes; Pre-service teachers; Primary education